Assessing the Differential Effects of Peer Tutoring for Tutors and Tutees - Allen Thurston; Maria Cockerill; Tien-Hui Chiang (MDPI AG, 2021)
There is strong evidence that peer tutoring, as a form of cooperative learning, has a positive impact on tutor and tutee outcomes. However, little previous research has been reported as to the differential effects of engaging in cooperative learning in dyads for peer tutors and peer tutees, respectively. A randomised controlled experimental study was undertaken involving 295, 11- to 13-year-old students, drawn from 12 classrooms, across three secondary/high schools situated in areas of low-socio-economic status, in the north east of England. In total, 146 students engaged in cooperative learning for a period of 12 weeks, and 149 students served as a comparison group. Gains were significantly greater on independent standardised reading comprehension tests for those engaged in cooperative learning than those in comparison classes, and greater for tutors than tutees. The results are explored by critically reflecting on the underlying theories of education that may be at play in classrooms using this form of cooperative learning.